Analysis of the Influence of Network Quality and Consumer Satisfaction on Indosat Ooredo Starter Pack Purchase Decisions, A Case Study on Adolescents in Balungtawun Village, Sukodadi District, Lamongan Regency - Ashari Arifin; Abid Muhtarom; Mohammad Yaskun (Sean Institute, 2025)
This study aims to determine the influence of network quality and consumer satisfaction on the purchase decision of Indosat internet starter pack, both partially and simultaneously, and to find out one of the most dominant independent variables (network quality and consumer satisfaction) that have the most dominant influence on purchase decisions. In this study, 100 samples were used from the adolescent population of Balungtawun village with purposive sampling technique. The method of data collection is by distributing questionnaires to adolescent consumers who have purchased or used the Indosat ooredo internet starter pack. Data analysis used validity test analysis tools, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation test, determination coefficient test, t test, and f test. The results of the study show that partially and simultaneously there is a significant relationship between network quality variables and consumer satisfaction on purchase decisions. And the most dominant variable that affects purchasing decisions is network quality.